Antidepressants use during pregnancy and child psychomotor, cognitive and language development at 2 years of age—Results from the 3D Cohort Study - Tanguay, Noémie; Abdelouahab, Nadia; Simard, Marie-Noelle; Séguin, Jean R.; Marc, Isabelle; Herba, Catherine M.; MacLeod, Andrea A. N.; Courtemanche, Yohann; Fraser, William D.; Muckle, Gina (Frontiers in Pharmacology, 2023)
Introduction: Approximately 5.5% of pregnant women take antidepressants. Studies on prenatal exposure to antidepressants reported no association with child cognition, and inconsistent results with motor function and language development. A limitation has been the failure to adjust for prenatal maternal distress. Objectives: Assess the associations between prenatal exposure to antidepressants and child development at age two, while adjusting for maternal depressive symptoms and stress during pregnancy. Explore indirect effects through birth complications and consider sex-specific associations. Methods: This is an ancillary study of the 3D (Design Develop, Discover) Study initiated during pregnancy. Data on antidepressants were collected through medication logs spanning the entire pregnancy. Depressive symptoms and stress were assessed each trimester of pregnancy by self-reported questionnaires, motor and cognitive development with the Bayley Scales of Infant and Toddler Development (BSID), and language development with the MacArthur Communicative Development Inventories at age 2. Multiple linear regressions were used to assess the associations between exposure and developmental outcomes. Mediation models were used to assess indirect effects. Interaction terms were introduced to assess sex-specific associations. Results: 1489 mother-child dyads were included, of whom 61 (4.1%) reported prenatal antidepressant use. Prenatal exposure was negatively associated with motor development (B = -0.91, 95% CI -1.73, -0.09 for fine motor, B = -0.89, 95% CI -1.81, 0.02 for gross motor), but not with cognitive (B = -0.53, 95% CI -1.82, 0.72) and language (B = 4.13, 95% CI -3.72, 11.89) development. Adjusting for maternal prenatal distress only slightly modified these associations. No indirect effect or differential effect according to child sex were found. Conclusions: This study supports evidence of a negative association between prenatal exposure to antidepressants and motor development at age two, after adjusting for maternal distress, but the effect size remains very small, with about only one BSID-III point lower in average.